Electron microscopy study on grain boundary characterizations of Fe–Co–V alloy during annealing. (April 2015) - Hasani, S.; Shamanian, M.; Shafyei, A.; Behjati, P.; Mostaan, H.; Sahu, P.; Szpunar, J.A.
Abstract: The present study investigates the microstructure and grain boundaries evolutions during recrystallization of commercial FeCo-∼7 wt.% V. The resulting microstructures were characterized using electron back scatter diffraction after annealing at different temperatures. At low temperatures (∼400 °C), where only recovery occurs during annealing, the fraction of low angle boundaries was increased. But, at high temperatures (∼850 °C), where recrystallization occurs during annealing, the fraction of high angle boundaries and low-Σ coincidence site lattice (CSL) boundaries (especially Σ3) were increased. Highlights: The microstructure and grain boundaries evolutions during recrystallization of commercial FeCo-7V. The fraction of high angle boundaries and low-Σ coincidence site lattice boundaries (especially Σ3). The microstructures evolution during annealing by EBSD and TEM.